Meta-Analysis of the Effect of Character Education Integration in Physics Learning Material on Student’s Learning Outcomes - Pratiwi Anwar; Asrizal Asrizal; Festiyed Festiyed (Universitas Negeri Padang, 2023)
Character is an urgent part for students to achieve success. However, the character value of students was still low. The solution to the problem is to integrate character education into learning materials. The purpose of this study was to investigate the effect of integrating character education into physics teaching material on student learning outcomes in the knowledge aspect. This type of research can be categorized into the method of meta-analysis. There are 22 national and international articles from 2013 to 2021 analyzed to determine the effect size. The data analysis technique is to calculate the effect size of each article. Based on the results of the study it is known that the integrated teaching materials for character education in physics teaching materials have a significant effect on learning outcomes on aspects of student knowledge. First, integrated teaching materials for the character education aspect of knowledge are very high, namely 1.76, in the class XI level category. Second, integrated teaching materials for character education provide a significant effect on learning outcomes in the knowledge aspect for the types of learning materials, namely teaching materials/teaching books with an effect size score of 1.96 in the high category. Third, integrated teaching materials for character education are effectively used at the high school level, namely work and energy, which has a score of 1.90. This means that the integrated learning material for character education have a significant effect both for class levels, types of learning materials, and learning materials.